Bioactive peptides and proteins for tissue repair: microenvironment modulation, rational delivery, and clinical potential - Zhuo-Wen Hao; Zhe-Yuan Zhang; Ze-Pu Wang; Ying Wang; Jia-Yao Chen; Tian-Hong Chen; Guang Shi; Han-Ke Li; Jun-Wu Wang; Min-Chao Dong; Li Hong; Jing-Feng Li (Military Medical Research)
Abstract Bioactive peptides and proteins (BAPPs) are promising therapeutic agents for tissue repair with considerable advantages, including multifunctionality, specificity, biocompatibility, and biodegradability. However, the high complexity of tissue microenvironments and their inherent deficiencies such as short half-live and susceptibility to enzymatic degradation, adversely affect their therapeutic efficacy and clinical applications. Investigating the fundamental mechanisms by which BAPPs modulate the microenvironment and developing rational delivery strategies are essential for optimizing their administration in distinct tissue repairs and facilitating clinical translation. This review initially focuses on the mechanisms through which BAPPs influence the microenvironment for tissue repair via reactive oxygen species, blood and lymphatic vessels, immune cells, and repair cells. Then, a variety of delivery platforms, including scaffolds and hydrogels, electrospun fibers, surface coatings, assisted particles, nanotubes, two-dimensional nanomaterials, and nanoparticles engineered cells, are summarized to incorporate BAPPs for effective tissue repair, modification strategies aimed at enhancing loading efficiencies and release kinetics are also reviewed. Additionally, the delivery of BAPPs can be precisely regulated by endogenous stimuli (glucose, reactive oxygen species, enzymes, pH) or exogenous stimuli (ultrasound, heat, light, magnetic field, and electric field) to achieve on-demand release tailored for specific tissue repair needs. Furthermore, this review focuses on the clinical potential of BAPPs in facilitating tissue repair across various types, including bone, cartilage, intervertebral discs, muscle, tendons, periodontal tissues, skin, myocardium, nervous system (encompassing brain, spinal cord, and peripheral nerve), endometrium, as well as ear and ocular tissue. Finally, current challenges and prospects are discussed.